A more secure and scalable routing protocol for mobile ad hoc networks - Qabajeh, L.K.; Kiah, M.L.M.; Qabajeh, M.M. (2012)
An essential problem in mobile ad hoc networks is finding an efficient and secure route from a source to an intended destination. In this paper, we have proposed a new model of routing protocol named ARANz, which is an extension of the original Authenticated Routing for Ad Hoc Networks (ARAN). ARANz adopts the authentication methods used with ARAN and aims to increase security, achieve robustness and solve the single point of failure and attack problems by introducing multiple local certificate authority servers. Additionally, via dealing with the network as zones and using restricted directional flooding, our new model exhibits better scalability and performance. Through simulation, we evaluated ARANz and compared it with the original ARAN as well as Ad Hoc On-demand Distance Vector. Simulation results show that ARANz is able to effectively discover secure routes within relatively large networks with large number of mobile nodes, while maintaining the minimum packet routing load. Copyright Â© 2012 John Wiley & Sons, Ltd.